2022
DOI: 10.1099/jmm.0.001520
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and Prevotella spp.: friend or foe? A systematic literature review

Abstract: During this global pandemic of the COVID-19 disease, a lot of information has arisen in the media and online without scientific validation, and among these is the possibility that this disease could be aggravated by a secondary bacterial infection such as Prevotella, as well as the interest or not in using azithromycin, a potentially active antimicrobial agent. The aim of this study was to carry out a systematic literature review, to prove or disprove these allegations by scientific arguments. The search inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 180 publications
(209 reference statements)
0
6
0
Order By: Relevance
“…And it also closely related to localized infection of ear and nose [ 27 , 28 ], inflammatory periodontitis [ 29 , 30 ], pulmonary infection [ 31 , 32 ], gastrointestinal infection [ 33 , 34 ] and some autoimmune diseases. Moreover, immunological interactions between Prevotella and viruses usually inducing an increase of pro-inflammatory responses [ 35 ]. Virulence factors including lipopolysaccharide [ 36 , 37 ], fimbriae [ 38 ], hemolysin [ 39 ] and adhesin [ 40 ] were found in Prevotella , which can promote its pathogenicity and survival in the host.…”
Section: Discussionmentioning
confidence: 99%
“…And it also closely related to localized infection of ear and nose [ 27 , 28 ], inflammatory periodontitis [ 29 , 30 ], pulmonary infection [ 31 , 32 ], gastrointestinal infection [ 33 , 34 ] and some autoimmune diseases. Moreover, immunological interactions between Prevotella and viruses usually inducing an increase of pro-inflammatory responses [ 35 ]. Virulence factors including lipopolysaccharide [ 36 , 37 ], fimbriae [ 38 ], hemolysin [ 39 ] and adhesin [ 40 ] were found in Prevotella , which can promote its pathogenicity and survival in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Prevotella has been enriched in other respiratory infections, including pulmonary empyema, lung abscess, inhalation pneumonia, chronic otitis, and sinusitis. 34 , 35 , 36 Prevotella has also been identified as one of the most prevalent bacterial populations in the oropharynx of HIV-positive patients. During COVID-19, the prevalence of Prevotella has been found to be higher in infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the abundance of Prevotella was positively correlated with hospitalized COVID-19. The increased Prevotella suggests the presence of a large number of viral infections, such as human immunodeficiency virus (HIV), papillomavirus (HPV), herpesvirus, and respiratory viruses [30]. Intriguingly, the increased abundance ofRuminococcus gnavus could not only be found in the respiratory tract, but also be reported to coincide with inflammatory bowel disease [31] [32] [33].…”
Section: Discussionmentioning
confidence: 99%